(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Aviation or air travel relates to the operations of the airlines and aircraft industries related to mechanical flights. We are presenting a recent literature survey on aviation management in this article. Airline Capability Analysis Air Traffic Flow Management Airline Fleet Assignment Tail Assignment with Aircraft Maintenance Routing Airline Crew Pairing Airline Recovery and Rescheduling Airline Revenue Management Joint Decision Making Aircraft Scheduling. The literature review is grouped into the following key categories This classification seeks to inspire aviation management researchers and practitioners to establish more important, practical and wider-ranging optimization methodologies to address the current needs of the aviation industry.